Advantages and Limitations of Surface Analysis Techniques on Plasma-Treated Arabidopsis thaliana Seeds - Waskow, Alexandra; Howling, Alan; Furno, Ivo (Frontiers in Materials, 2021)
Surface characterization of plasma-treated seeds has made significant progress over the last decade. Most papers in the literature use scanning electron microscopy (SEM) and contact angle goniometry to investigate surface modifications. However, very few papers address the chemical modifications to the seed coat after plasma treatment. Here, a summary of the methods used to analyze plasma-treated seeds is presented, such as SEM, contact angle goniometry, energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), atomic force microscopy (AFM) and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). The results obtained on Arabidopsis thaliana Col-0 seeds and the limitations of these techniques are discussed. An experiment was designed in order to compare the relative advantages and limitations of these surface analysis techniques by investigating the separate effects of plasma, heat, and ozone on Arabidopsis thaliana seeds.